Economic Evaluation of the Implementation of Policy Actions in the Field of Energy Efficiency - Vitliemov, Pavel; Kolev, Nikolay; Marinov, Milko (International Journal of Energy Economics and Policy, 2019)
This paper presented an analytical tool, based on the cost-benefit analysis instrument, intended to be used to estimate both the financial and economic impacts related to the implementation of policy actions and/or projects (interventions) in the field of energy efficiency. The proposed guidelines are intended to provide relevant information and guidance on why and how to conduct financial and economic assessment to a relatively large number of institutions involved in the preparation and appraisal of energy efficiency actions Keywords: Economic, Evaluation, Policy, Energy, Efficiency JEL Classifications: P18; Q51; Q58 DOI: https://doi.org/10.32479/ijeep.7719